Lipid profile and renal safety of tenofovir disoproxil fumarate-based anti-retroviral therapy in HIV-infected Chinese patients. (June 2019) - Yang, Junyang; Chen, Jun; Ji, Yongjia; Tang, Qi; Zhang, Renfang; Liu, Li; Shen, Yinzhong; Xun, Jingna; Song, Wei; Tang, Yang; Wang, Zhenyan; Qi, Tangkai; et al.
Highlights: Triple anti-HIV therapy with TDF as the backbone is of good therapeutic effect among Chinese PLWH. TDF based regimens showed better plasma lipid profile with mild renal dysfunction as compared to non-TDF based regimens. Patients with high BMI, high baseline TG, and taking PIs were associated with hypertriglyceridemia. Abstract: Background: Tenofovir disoproxil fumarate (TDF) is an important component of antiretroviral therapy (ART) that has been widely used. The aim of this study was to observe the long-term impact of TDF-based ART on lipid metabolism profiles and renal functions in Chinese patients. Methods: 414 and 124 HIV-infected, ART-naïve patients who initiated TDF-based regimens and non-TDF regimens respectively were retrospectively included. Demographic characteristics and clinical information of each patient was collected. Changes of lipid profiles and renal function, as well as the risk factors of hyperlipidemia and renal dysfunction were analyzed. Results: After 96 weeks of ART, HIV viral loads were undetectable in 97.34% (403/414) of patients exposed to TDF. The plasma total cholesterol (TCH) increased from 3.97 ± 0.83 mmol/L to 4.53 ± 0.87 mmol/L ( P < 0.001), which did not show a significant difference comparing with non-TDF exposed group. By contrast, the plasma triglyceride (TG) levels increased, but were still lower than that in the non-TDF exposed group (0.26 ± 1.24 vs. 0.89 ± 1.78, P < 0.001). The mean estimated glomerular filtration rate (eGFR) decreased from 127.29 ± 24.04ml∙min −1 ∙1.73 m −2 at baseline to 118.84 ± 22.74 ml∙min −1 ∙1.73 m −2 ( P < 0.001) in the TDF exposed group, while it increased in the non-TDF exposed group. In the TDF group, high body mass index (BMI) (OR = 1.13, P = 0.01), high baseline TG (OR = 2.33, P <0.001) and receiving protease inhibitors (PIs) (OR = 7.58, P < 0.001) were associated with hypertriglyceridemia after ART, while high baseline TCH predicted hypercholesterolemia (OR = 3.58, P < 0.001). MSM (OR = 0.22, P = 0.02) and baseline eGFR (OR = 0.90, P < 0.001) was associated with renal dysfunction after ART. Conclusions: TDF-based regimens are of good therapeutic effect among Chinese people. These regimens showed a better plasma lipid profile but mild renal dysfunction as compared to non-TDF based regimens. Patients with high BMI, high baseline TG, high baseline TCH and low baseline eGFR should be closely monitored when using TDF-based ART.